p53 Rather Than β-Catenin Mediated the Combined Hypoglycemic Effect of Cinnamomum cassia (L.) and Zingiber officinale Roscoe in the Streptozotocin-Induced Diabetic Model - Nasra Ayuob; Mona Ramadan Al-Shathly; Abdulaziz Bakhshwin; Nouf Saeed Al-Abbas; Nehad A Shaer; Soad Al Jaouni; Walaa H. E. Hamed (Frontiers Media S.A., 2021)
Background: The antioxidant, hypoglycemic, and insulin-enhancing effects of ginger and cinnamon were previously confirmed in experimental and human studies, while the combined effect of ginger and cinnamon was not thoroughly investigated until now.Objectives: This study was designed to assess the antidiabetic effect of combined administration of ginger (Zingiber officinale Roscoe) and cinnamon (Cinnamomum cassia L.) in streptozotocin (STZ)-induced diabetic rats compared to metformin and to explain the mechanism behind this effect.Materials and methods: STZ was utilized to induce diabetes mellitus in male Sprague-Dawley rats. Assessments of fasting blood glucose level (BGL), the total antioxidant capacity (TAC), serum insulin, HOMA-IR, and HOMA-β cells were performed. Pancreatic gene expression of β-catenin and p53 was assessed using RT-PCR. Assessment of histopathological alterations of pancreatic islet cells was performed using routine and immunohistochemical techniques.Results: BGL significantly decreased (p = 0.01), while serum insulin and TAC significantly increased (p < 0.001) in both metformin- and ginger plus cinnamon-treated groups compared to the untreated diabetic group. HOMA-β cell index significantly increased (p = 0.001) in ginger plus cinnamon, indicating their enhancing effect on insulin secretion in diabetic conditions. p53 gene expression was significantly upregulated (p < 0.001), while β-catenin was insignificantly downregulated (p = 0.32) in ginger plus cinnamon-treated groups. Insulin immunoexpression in β cells significantly increased (p = 0.001, p = 0.004) in metformin- and ginger plus cinnamon-treated groups, respectively.Conclusions: The combined administration of ginger and cinnamon has a significant hypoglycemic and antioxidant effect in STZ-induced diabetes mostly through enhancing repair of islet cells mediated via upregulation of pancreatic p53 expression. Therefore, testing this effect in diabetic patients is recommended.